Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1371/journal.pgen.1002312
|View full text |Cite
|
Sign up to set email alerts
|

Von Hippel-Lindau (VHL) Inactivation in Sporadic Clear Cell Renal Cancer: Associations with Germline VHL Polymorphisms and Etiologic Risk Factors

Abstract: Renal tumor heterogeneity studies have utilized the von Hippel-Lindau VHL gene to classify disease into molecularly defined subtypes to examine associations with etiologic risk factors and prognosis. The aim of this study was to provide a comprehensive analysis of VHL inactivation in clear cell renal tumors (ccRCC) and to evaluate relationships between VHL inactivation subgroups with renal cancer risk factors and VHL germline single nucleotide polymorphisms (SNPs). VHL genetic and epigenetic inactivation was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(139 citation statements)
references
References 50 publications
3
129
1
4
Order By: Relevance
“…Somatic inactivation of VHL, which was originally identified in the hereditary cancer syndrome von HippelLindau (VHL) disease 19 , is very common in ccRCC (~52% of patients) 4 . The majority of the inactivating events are point mutations 4,15,20,21 . The VHL disease tumour suppressor protein (pVHL) has multiple functions 22 , and is best known as a regulator of oxygen and energy sensing via the targeted degradation of the hypoxia-inducible factors (HIF) 1 and HIF2 [Au: Refs OK?].…”
Section: Epidemiology and Genetics Of Renal Cancermentioning
confidence: 99%
“…Somatic inactivation of VHL, which was originally identified in the hereditary cancer syndrome von HippelLindau (VHL) disease 19 , is very common in ccRCC (~52% of patients) 4 . The majority of the inactivating events are point mutations 4,15,20,21 . The VHL disease tumour suppressor protein (pVHL) has multiple functions 22 , and is best known as a regulator of oxygen and energy sensing via the targeted degradation of the hypoxia-inducible factors (HIF) 1 and HIF2 [Au: Refs OK?].…”
Section: Epidemiology and Genetics Of Renal Cancermentioning
confidence: 99%
“…Because of VHL is mutated or silenced in >50% of CCRCC [17], we asked whether the decreased Prx3 is related to VHL. RCC4 which is a VHL defective cell line derived from CCRCC and RCC4 with stable re-expression of VHL (RCC4/VHL) were tested by quantitative real-time PCR and western blot, respectively.…”
Section: Ccrcc Tissues Present Lower Expression Of Prx3 That Can Be Rmentioning
confidence: 99%
“…Although the ccRCC-defining loss of function of the von Hippel-Lindau gene (VHL) was thought uncommon in nccRCC, a recent study reported an incidence of ∼16% in sporadic cases [5]. Moreover, amplification or activating mutations in MET (encoding the hepatocyte growth factor [HGF] receptor), found in a subset of patients with sporadic papillary RCC (the most common nccRCC type), often result in tumor hypoxia, leading to overexpression of angiogenic mediators.…”
Section: Introductionmentioning
confidence: 99%